Petalidium karasbergense (Acanthaceae), a new species from Namibia - Swanepoel, Wessel; Wyk, Abraham E. Van (Phytotaxa, 2023)
Petalidium karasbergense, here described as a new species, is only known from the Groot Karasberge (Great Karas Mountains) in southeastern Namibia where it grows on arid hillsides in dwarf shrubland. Diagnostic morphological characters for P. karasbergense include the rigid, tapering and often spinescent distal stems and lateral branchlets, grey, grey-white or grey-black bark (white to cream when young), strigulose, glabrescent vegetative parts, oblanceolate to narrowly obovate leaves, and the free to almost free bracteole pairs (not connate at the base). A comparison of some of the more prominent features to differentiate Petalidium karasbergense from P. parvifolium, its morphologically most similar relative, and P. lucens with which its distribution range marginally overlaps, is provided. Based on IUCN Red List categories and criteria, a conservation assessment of Vulnerable VU D1 is recommended for the new species.